2018
DOI: 10.1177/0956797618768058
|View full text |Cite
|
Sign up to set email alerts
|

How Much Is Enough in a Perfect World? Cultural Variation in Ideal Levels of Happiness, Pleasure, Freedom, Health, Self-Esteem, Longevity, and Intelligence

Abstract: The maximization principle-that people aspire to the highest possible level of something good if all practical constraints are removed-is a common yet untested assumption about human nature. We predict that in holistic cultures-where contradiction, change, and context are emphasized-ideal states of being for the self will be more moderate than in other cultures. In two studies ( Ns = 2,392 and 6,239), we asked this question: If participants could choose their ideal level of happiness, pleasure, freedom, health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 37 publications
2
45
0
5
Order By: Relevance
“…Most recommendations are based, however, on measuring the societal well‐being of individuals using constructs developed in individualistic cultures (i.e., individual life satisfaction). The assumption that this type of well‐being is universally valued and desired may not be correct (Diener, Napa‐Scollon, Oishi, Dzokoto, & Suh, ; Hornsey et al., ; Joshanloo & Weijers, ; Krys et al, ). Our findings suggest that we may need to elaborate and more thoroughly study societal well‐being that is less culture‐bound.…”
Section: Discussionmentioning
confidence: 99%
“…Most recommendations are based, however, on measuring the societal well‐being of individuals using constructs developed in individualistic cultures (i.e., individual life satisfaction). The assumption that this type of well‐being is universally valued and desired may not be correct (Diener, Napa‐Scollon, Oishi, Dzokoto, & Suh, ; Hornsey et al., ; Joshanloo & Weijers, ; Krys et al, ). Our findings suggest that we may need to elaborate and more thoroughly study societal well‐being that is less culture‐bound.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous studies implicitly assume that all people prefer to be well, but fewer studies (Hornsey et al 2018;Koh 2014) explicitly acknowledge that people may value wellbeing to various extents. Even if different well-beings contribute to each other, people (in particular, from various cultural backgrounds) do differently value various types of well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Such positive evaluations of life satisfaction are common among individuals shaped by Western, Educated, Industrialized, Rich and Democratic societies (WEIRD; Henrich et al 2010), and are implicitly assumed to apply to the whole human race. In contrast, some psychological research hints that well-being may be defined, experienced, and valued differently across individuals and cultures (Delle Fave et al 2016;Hornsey et al 2018;Lu and Gilmour 2004;Uchida and Oishi 2016). For example, in contrast to researchers' typical focus on life satisfaction, a more open-ended approach by Delle Fave and collaborators (2016) revealed that harmony and balance were mentioned more often than satisfaction among lay definitions of happiness.…”
Section: Well-being Valuation Varies Across Culturesmentioning
confidence: 98%
See 2 more Smart Citations